2016
DOI: 10.1111/cei.12770
|View full text |Cite
|
Sign up to set email alerts
|

Abundant cytomegalovirus (CMV) reactive clonotypes in the CD8+ T cell receptor alpha repertoire following allogeneic transplantation

Abstract: SummaryAllogeneic stem cell transplantation is potentially curative, but associated with post-transplantation complications, including cytomegalovirus (CMV) infections. An effective immune response requires T cells recognizing CMV epitopes via their T cell receptors (TCRs). Little is known about the TCR repertoire, in particular the TCR-a repertoire and its clinical relevance in patients following stem cell transplantation. Using next-generation sequencing we examined the TCR-a repertoire of CD8 T cells and ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 39 publications
3
25
0
Order By: Relevance
“…By contrast, previous studies showed structures of either TCRs against an artificial ligand from genetically different mice 47 , different individuals 27 , or TCRs that reflect limited repertoire to the viral epitopes at the individual or population level 28,29 . Deep sequencing of TRBV repertoire has been examined for some viral epitopes 25 and TRAV analyses have been examined in CMV-specific responses of 2 donors 26 . However, there are no reports where human viral antigen-specific TCR repertoires have been characterized for both TRBV and TRAV sequences by NGS sequencing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, previous studies showed structures of either TCRs against an artificial ligand from genetically different mice 47 , different individuals 27 , or TCRs that reflect limited repertoire to the viral epitopes at the individual or population level 28,29 . Deep sequencing of TRBV repertoire has been examined for some viral epitopes 25 and TRAV analyses have been examined in CMV-specific responses of 2 donors 26 . However, there are no reports where human viral antigen-specific TCR repertoires have been characterized for both TRBV and TRAV sequences by NGS sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, SIV viral load was inversely correlated not with epitope-specific CD8 T cell frequency, recruitment to target organ, multifunctionality, or inability to recognize mutated virus, but rather with the number of public TCR clonotypes 23 , implying that the size of the TCR repertoire may be a critical component to understand efficient viral control. Despite the increasing availability of high-throughput TCR sequencing strategies 24 the breadth of TCR responding to human viral infection has been studied only in a few cases at sequence 25,26 or structural levels 2729 and no study has been reported that combines both aspects.…”
mentioning
confidence: 99%
“…1, Yang et al, 2015; 2, Trautmann et al, 2005; 3, Link et al, 2016; 4, Gras et al, 2009; 5, Nguyen et al, 2014; 6, Schub et al, 2009; 7, Moss et al, 1991; 8, Ishizuka et al, 2008; 9, Stewart-Jones et al, 2003; N, newly identified pairs in this study.…”
Section: Figurementioning
confidence: 92%
“…75 These expanded clones are largely CMV specifiC-terminally differentiated effector cells as measured by gene expression analysis and TCR sequencing of single cells sorted by flow cytometry. 74 Early clonal expansion produces a period of oligoclonality with a small number of CMV specific clones comprising a large proportion of all CD8…”
Section: Factors Influencing CMV Immunity Post Transplantmentioning
confidence: 99%
“…It is possible that this represents expansion of clones transferred with the graft on exposure to antigen in the host. 74 Later in the recovery process the TCR diversity expands with new clones derived from stem cell graft progenitors. 66 CMV serostatus has a strong impact on the pattern of global immune recovery, such as the ratio of B cells to T and NK cells, in addition to the well known effects on T lymphocytes.…”
Section: Factors Influencing CMV Immunity Post Transplantmentioning
confidence: 99%